Physicochemical and structural characterization of Lima Bean (Phaseolus lunatus) globulins - Chel-Guerrero, Luis (2007)
A globulin fraction from Phaseolus lunatus have been isolated and characterized. The fractionation scheme used allowed to obtain a Globulin partially purificated. Globulin purification by ultracentrifugation allowed to isolate three peaks with different sedimentation coefficient, while gel filtration chromatography yielded two species, I and II, which were later identified as 11S and 7S globulins, respectively. Species II, 7S globulin from P. lunatus, seems to have a molecular mass of 72 kDa and to be constituted by polypeptides of 34–36, 25–27 and 16–18 kDa without intermolecular disulfide bonds. These polypeptides would present certain heterogeneity, as suggested by the results of isoelectric focusing and electrophoresis analyses. This protein exhibited some particular features, including a lower molecular mass and higher thermal stability than typical vicilins. Species I, with a molecular mass of 336 kDa, would be constituted by subunits of 53–55 and 40–41 kDa formed by smaller polypeptides (around 30 and 20 kDa) linked by disulfide bonds. These features, together with the existence of basic and acid polypeptides in the molecule, would confirm that species I is a globulin of the legumins, 11S globulins or -conglutin family.